1999
DOI: 10.1177/107602969900500208
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-Art Review : Evaluation of the Clot Signature Analyzer as a Hemostasis Test in Healthy Volunteers Exposed to Low Doses of Aspirin

Abstract: Several variables affect bleeding time that make it difficult to obtain consistent measurements. The Clot Signature Analyzer (CSA) has been developed to assess in vitro hemostasis using well-controlled flow chambers. In this study, the equivalencies in the CSA parameters with the conventional bleeding time or platelet aggregation methods were evaluated in subjects exposed to aspirin. The CSA parameters, platelet hemostasis time (PHT) and collagen-induced thrombus formation (CITF), were compared to bleeding tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The few studies on the sensitivity of the CSA for the detection of antiplatelet drug effects have not been encouraging. Igawa et al found that in 53 normal volunteers, the PHT increased following the ingestion of low doses of aspirin 56 . However, the coefficient of variation for the PHT was very wide (49 to 65%) and the CITF showed little change.…”
Section: Clot Signature Analyser ®mentioning
confidence: 99%
“…The few studies on the sensitivity of the CSA for the detection of antiplatelet drug effects have not been encouraging. Igawa et al found that in 53 normal volunteers, the PHT increased following the ingestion of low doses of aspirin 56 . However, the coefficient of variation for the PHT was very wide (49 to 65%) and the CITF showed little change.…”
Section: Clot Signature Analyser ®mentioning
confidence: 99%
“…We therefore decided to use CSA to assess information about platelet function (represented by the parameters, PHT and CITF) and coagulation processes (CT). CSA has been used previously for determination of clinical clotting disorders, [17][18][19] but not in the setting of surgery. To our knowledge, our findings represent the first time a coagulation test was able to demonstrate that orthopedic surgery induces hypercoagulability, and that the use of EA prevents this effect.…”
Section: Discussionmentioning
confidence: 99%